Intervensi Psikologi Pendidikan untuk Mengurangi Kecemasan Asesmen di Kalangan Santri Pesantren - Sariman, Sariman; Mutaqien, Faiz Zaenal (Al Fattah Ejournal Sma Al Muhammad Cepu, 2025)
Academic anxiety experienced by pesantren students in facing assessment often disrupts their concentration and affects the quality of their learning. This study aims to identify the effectiveness of educational psychology interventions in reducing assessment anxiety in pesantren students. This study used a qualitative approach with a descriptive design. The main data sources were obtained through in-depth interviews with 15 santri who experienced anxiety related to assessment, as well as pesantren managers who were involved in the implementation of the intervention programme. Data were also obtained through observation of the learning dynamics in the pesantren. The results showed that educational psychology interventions, which included relaxation techniques, stress management, and cognitive-behavioral approaches, were effective in reducing academic anxiety among santri. Students who received the psychology training showed a significant reduction in anxiety levels, as well as an improved ability to manage stress before exams. However, external factors such as social pressure from peers and family expectations still influence the level of anxiety felt by santri. This study suggests the need for a more comprehensive approach, involving the role of family and the pesantren community in supporting the management of academic anxiety.